Increased sagittal abdominal diameter is associated with a higher risk of kidney stones. - Wei Song; Shugen Li; Guangchun Wang; Shang Gao (PLoS ONE)
Background This study investigates the relationship between sagittal abdominal diameter (SAD), a measure of abdominal obesity, and kidney stone disease (KSD) in the U.S. population. Additionally, it explores potential underlying mechanisms and evaluates the clinical utility of a predictive model. Methods Data were collected from 11,671 participants, including 1,136 cases of KSD. Univariate and multivariate logistic regression analyses, dose-response curves, and mediation effect assessments were employed to examine the association between SAD and KSD. A predictive model was developed and validated using calibration curves, receiver operating characteristic (ROC) curves, and clinical decision curves. Additionally, hematological indicators were analyzed to identify potential mediating factors. Results SAD showed a strong and positive association with KSD, even after adjusting for confounders such as gender, age, and education. The predictive model demonstrated moderate accuracy (AUC =  0.661) and clinical utility. Hematological analyses indicated that granulocyte count (GRAN) significantly mediated the relationship between SAD and KSD (P <  0.001). Conclusions SAD is a significant risk factor for KSD, underscoring the role of abdominal obesity in kidney stone formation. The predictive model demonstrates potential clinical applications for early risk assessment and management of KSD.